Dynamic phase separation of confined driven particles. (21st August 2017) - Kusters, R.; Storm, C.
Abstract: Even a small number of actively driven particles can set large numbers of passive particles into motion. We study collective behavior in densely packed particle systems, that contain a minority fraction of driven particles. We observe a dynamical phase separation, determined by driving force, density and temperature, that manifests itself in the clustering, into tight bands, of the driven particles. We determine the critical conditions for this phase separation and provide a simple physical picture that explains the formation and subsequent growth of a compacted zone developing in front of the driven cluster. We analyze the implications of this clustering transition for driven transport in dense particulate flows; a nonmonotonic dependence of the average velocity on the driving force makes this process difficult to optimize.